2009
DOI: 10.1128/jcm.00027-09
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic of Postsurgical Infections Caused by Mycobacterium massiliense

Abstract: An epidemic of infections after video-assisted surgery (1,051 possible cases) caused by rapidly growing mycobacteria (RGM) and involving 63 hospitals in the state of Rio de Janeiro, Brazil, occurred between August 2006 and July 2007. One hundred ninety-seven cases were confirmed by positive acid-fast staining and/or culture techniques. Thirty-eight hospitals had cases confirmed by mycobacterial culture, with a total of 148 available isolates recovered from 146 patients. Most (n ‫؍‬ 144; 97.2%) isolates present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
208
1
25

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 200 publications
(242 citation statements)
references
References 41 publications
8
208
1
25
Order By: Relevance
“…Representative isolates were identified as M. massiliense and belonged to a single clone named BRA100, which was genotypically identical to isolates obtained from previous outbreaks. Our results showed that M. massiliense BRA100 strain was also resistant to 2% glutaraldehyde (GTA) commercial solutions, commonly used for preoperative high-level disinfection in Brazil 10,11 .…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Representative isolates were identified as M. massiliense and belonged to a single clone named BRA100, which was genotypically identical to isolates obtained from previous outbreaks. Our results showed that M. massiliense BRA100 strain was also resistant to 2% glutaraldehyde (GTA) commercial solutions, commonly used for preoperative high-level disinfection in Brazil 10,11 .…”
Section: Introductionmentioning
confidence: 87%
“…Representative isolates (CRM -0018 and CRM -0019), recovered from biopsies during the epidemic of postsurgical infections after videolaparoscopic procedures in the state of Rio de Janeiro (2006)(2007), and previously identified as belonging to M. massiliense BRA100 strain were used for this investigation 10 . Additionally, M. massiliense isolate (CRM -270) obtained from sputum of non-epidemiologically related patient and not belonging to BRA100 clone was also evaluated.…”
Section: Mycobacterial Isolatesmentioning
confidence: 99%
See 3 more Smart Citations